THE EFFECT OF CONCENTRATION AND DURATION OF SOAKING SHALLOT BARK SOLUTION ON ROOT FORMATION OF CUTTINGS OF CHRYSANTHEMUM KULO (Chryshanthemum sp.) IN TOMOHON CITY - MARTHA FERA DELLASTRADA GARING; Adeleyda M. W. Lumingkewas; Selvie Tumbelaka (Sam Ratulangi University, 2021)
Chrysanthemum kulo plant is a variety native to The City of Tomohon which has a high aesthetic and economic value. Good quality chrysanthemum plant seeds can be obtained through vegetative multiplication techniques. One of the vegetative multiplication techniques is cuttings. The problem with the propagation of cuttings is that the rooting is less dense, so it can not hold the plant to grow upright. One source of natural growing regulators that can support the formation of roots is shallot bark. Shallot bark contains ABA, IAA, GA, Cytokinin. The purpose of this study was to study the interaction between concentration and length of soaking of shallot bark solution against the formation of cuttings root chrysanthemum shoots. This research was conducted in March 2021 until May 2021 at Screen House, Nursery, And Agrowidya Seeding Center of Tomohon City Tourism, Agriculture and Fisheries Office of Tomohon City. The design used is a Complete Randomized Design (RAL) Factorial with two factors, namely the first factor of concentration of shallot bark solution (K) consisting of 5 levels of 0%, 25%, 50%, 75%, 100% and the second factor soaking the shallot bark solution (T) consisting of 3 levels of 10 minutes, 20 minutes, 30 minutes. The variables measured are the percentage of root formation (%), the number of roots, and the length of the root (cm). Keywords: Chrysanthemum plants; Cuttings; Roots; Concentration, Shallot Bark.AbstrakTanaman krisan kulo merupakan varietas asli dari Kota Tomohon yang memiliki nilai estetika dan ekonomis yang tinggi. Bibit tanaman krisan yang berkualitas baik dapat diperoleh melalui teknik perbanyakan secara vegetatif. Salah satu teknik perbanyakan secara vegetatif ialah stek. Masalah pada perbanyakan stek yaitu perakaran yang kurang lebat, sehingga tidak dapat menahan tanaman untuk tumbuh dengan tegak. Salah satu sumber zat pengatur tumbuh alami yang dapat mendukung pembentukan akar adalah kulit bawang merah. Kulit bawang merah mengandung ABA, IAA, GA, Sitokinin. Tujuan dari penelitian ini adalah untuk mempelajari interaksi antara konsentrasi dan lama perendaman larutan kulit bawang merah terhadap pembentukan akar stek pucuk tanaman krisan. Penelitian ini dilaksanakan pada bulan Maret 2021 sampai bulan Mei 2021 di Screen House, Balai Perbenihan Pembibitan dan Agrowidya Wisata Kota Tomohon, Dinas Pertanian dan Perikanan Kota Tomohon. Rancangan yang digunakan adalah Rancangan Acak Lengkap (RAL) Faktorial dengan dua faktor yaitu pertama faktor konsentrasi larutan kulit bawang merah (K) yang terdiri dari 5 taraf 0%, 25%, 50%, 75%, 100% dan faktor yang kedua lama perendaman larutan kulit bawang merah (T) yang terdiri dari 3 taraf yaitu 10 menit, 20 menit, 30 menit. Variabel yang diukur adalah persentase pembentukan akar (%), jumlah akar, dan panjang akar (cm).Kata Kunci: Tanaman krisan; Stek; Akar; Konsentrasi; Kulit Bawang Merah.